Immunotherapies versus small-molecule therapies of cancers with RAS oncogene mutations - Rieske, Piotr (Alergologia Polska - Polish Journal of Allergology, 2025)
In recent years, it has become common for oncologists to compare the effects of small-molecule targeted therapies with immunotherapies. There are even no confrontational comparisons. The situation is similar for cancers exhibiting mutations of the RAS gene. However, it turns out that these cancers offer a unique opportunity to combine these two therapeutic interventions. Immunotherapy provides a possibility to overcome drug resistance to small-molecule compounds, but small-molecule therapy can sometimes facilitate the development of immunotherapies that overcome such drug resistance. The best-described example is the combination of covalent (irreversible) small-molecule therapy, against the RASG12C mutant, with immunotherapy relying on an antibody that recognizes the neoantigen, within which the covalent small-molecule compound (the blocker against which the drug resistance applies) is present.